Pomalidomide in the treatment of multiple myeloma: design, development and place in therapy - Rios-Tamayo R; Martín-García A; Alarcón-Payer C; Sánchez-Rodríguez D; Guardia AM; García Collado CG; Jiménez Morales A; Jurado Chacón M; Cabeza Barrera J (Dove Medical Press, 2017)
Rafael Ríos-Tamayo,1–4 Agustín Martín-García,5,6 Carolina Alarcón-Payer,5 Dolores Sánchez-Rodríguez,1,7 Ana María del Valle Díaz de la Guardia,5 Carlos Gustavo García Collado,5 Alberto Jiménez Morales,5 Manuel Jurado Chacón,1–4 José Cabeza Barrera4,5 1Monoclonal Gammopathies Unit, 2Department of Hematology, University Hospital Virgen de las Nieves, Granada, Spain; 3Genomic Oncology Area, GENYO, Center for Genomics and Oncological Research: Pfizer/University of Granada/Andalusian Regional Government, PTS, Granada, Spain; 4Instituto de Investigación Biosanitaria de Granada (Ibs.GRANADA), Hospitales Universitarios de Granada/Universidad de Granada, Granada, Spain; 5Department of Pharmacy, 6Clinical Trials Unit, University Hospital Virgen de las Nieves, Granada, Spain; 7FIBAO, Granada, Spain Abstract: Multiple myeloma is a very heterogeneous disease with variable survival. Despite recent progress and the widespread use of new agents, patients with relapsed and refractory disease have a poor outcome. Immunomodulatory drugs play a key role in both the front-line and the relapsed/refractory setting. The combination of pomalidomide (POM) and dexamethasone is safe and effective in relapsed and refractory patients, even in those with high-risk cytogenetic features. Furthermore, it can be used in most patients without the need to adjust according to the degree of renal failure. In order to further improve the results, POM-based triplet therapies are currently used. This article highlights the most relevant issues of POM and POM-based combinations in the relapsed/refractory multiple myeloma setting, from a pharmacological and clinical point of view. Keywords: multiple myeloma, pomalidomide, triplet therapy, dexamethasone